Current effectiveness of non- monetary incentives as a tool for Employee recognition in Great Wall Ceramic Industries Ltd. - Sarawari, Kaniz (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.